KONSEPSI LONTARA’ PABBURA DAN TIB AL-NABAWIY: KONTINUITAS DAN DISKONTINUITAS TRADISI PENGOBATAN PADA MASYARAKAT BONE - Ruslan Ruslan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This study examines the conception of lontara’ pabbura and tib al-nabawiy by seeing its continuity as a tradition of medicine in society. There are three problems to be answered. First, how is the conception of the disease and treatment practices contained in lontara 'pabbura. Second, how medical knowledge in lontara’ pabbura is practiced in the Bugis society; and third, how is the continuity of lontara 'pabbura treatment with tib al-nabawiy. This research is descriptive in nature, using observational methods, document studies, and interviews. The results of the research show that in the Lontara’ Pabbura document there are various information about the causes of disease and what is more differentiating from medical theory is that disease can arise not only because of viruses or bacteria, but because of factors from supernatural forces. In the practice of lontara’-based medicine, there are three forms of treatment carried out namely, through mantras or incantations, herbs, and Islamic prayer. It turns out that at this time, the concern of the Bugis Bone community for lontara pabbura-based treatment is very limited, due to several factors. First, because of the lack of attention to the lontara 'pabbura publication in Bone. Second, public awareness of the importance of medical treatment and Islamic medicine began to open. Third, the stigma of some people towards the method of treatment in lontara’ pabbura which considers something to do with syncretism. Lontara’-based treatment 'began to be excluded or weakened so that it could be said to be threatened. In contrast to tib al-nabawiy treatment, it actually shows signs of continuity that will be increasingly visible and strong in the community of Bone, because of the emergence of tib al-nabawiy-based treatment places openly. The results of this study suggest the need to preserve Lontara’-based education through educational institutions both formal and non formal